Socialization Awarness of Healty Living and Mentoring the Making of Creative Products Using Domestic Waste in Mayasopa, Singkawang in 2017 - Wahyuni Oktavia; Fajar Wulandari; Rini Setyowati; Safrihady Safrihady; Heru Susanto (STKIP Singkawang, 2018)
Service activities in the community in the form of socialization awareness of healthy living and advocacy make creative products using domestic waste aims to provide skills to the public regarding the management of household waste into environmentally damaging waste and can be used to make a variety of creative products of high value. Besides these activities also aim to provide an understanding and knowledge of the importance of raising the awareness of health and living a healthy lifestyle, create and encourage people to adopt healthy life. The target audience for the activities of PKK PPM is Mayasopa villages totaling 26 people. Socialization and mentoring are done by lectures, demonstrations, discussions, and exercises with frequently asked questions. The availability of sufficient expertise in mentoring and socialization creative product making healthy lifestyle, the enthusiasm of the participants, the support of the Village, RT, and RW to the implementation and support of STKIP Singkawang fund is supporting the implementation of this PPM activities. The constraints faced by the participants are yet to have prior knowledge about the making of the product and determine the implementation schedule of activities because trainees have busy each of them work in the fields, gardens and more. The benefits can be obtained by the participants of this PPM among others, can .memahamipentingnya health and a healthy lifestyle at the same time adopting a healthy lifestyle. Moreover, this activity provides awareness on the PKK in the Village Mayasopa how to take advantage of used goods into a product that can improve the economics of the family.